2022
DOI: 10.1016/j.jiac.2021.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from severe persistent COVID-19 without evidence of an anti-SARS-CoV-2 antibody response in a man with mantle cell lymphoma treated with rituximab

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…However, several case reports of persistent COVID-19 have shown that immunocompromised patients did not improve with remdesivir alone ( 1 , 3 - 6 , 8 , 12 , 15 , 16 ). In a recent report of patients hospitalized with COVID-19, REGEN-COV reduced the 28-day mortality rate ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several case reports of persistent COVID-19 have shown that immunocompromised patients did not improve with remdesivir alone ( 1 , 3 - 6 , 8 , 12 , 15 , 16 ). In a recent report of patients hospitalized with COVID-19, REGEN-COV reduced the 28-day mortality rate ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Persistent SARS-CoV-2 infection may occur in immunocompromised individuals, and these patients tend to remain infectious for !3 weeks. Table 2 lists reported cases of persistent SARS-CoV-2 infection in patients under anti-CD20 therapy, including this case (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Most case reports are of malignant lymphoma or chronic lymphocytic leukemia, and rarely of other diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appropriateness of using anti-CD20 monoclonal antibody rituximab remains controversial because of its negative impact on the production of nAb against COVID-19, 21–23 although the role of nAb in patients recovering from COVID-19 infection also remains controversial. 10 , 21 , 24 Because of the high risk of thrombotic complications with COVID-19 infection, 25 , 26 the use of thrombopoietin receptor agonists when managing ITP during infection with COVID-19 requires caution. Of the 13 reported patients, 4 received prophylactic anticoagulants and none reported thrombotic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Four patients cleared SARS-CoV-2, and one patient passed away after a prolonged hospital stay after. Another case was successfully treated with interferon beta-1b in combination with RDV and IVIg [74].…”
Section: Othermentioning
confidence: 99%